Information Systems Analysis as a Preliminary Study for Smart Campus Development - Titis Sari Putri; Mohammad Rezza Fahlevvi; Muhammad Tosan Bingamawa; Ikra Novar Rizqi; Megandaru Widhi Kawuryan (Universitas Islam Indragiri, 2026)
The trend of smart campus development has increased over the past 10 years, marked by digital transformation and the implementation of IoT and big data. This trend is not limited to state and private universities; civil service universities are also participating in the development of smart campuses. Unlike state and private universities, civil service universities face limitations in internal institutional management that pose significant challenges for planning and building large projects, such as smart campuses. The smart campus development plan at the Institut Pemerintahan Dalam Negeri (IPDN) is still hampered by various issues related to the management of scattered information and low use of information systems within the campus environment. Various stakeholders hold different opinions on these issues, so the nature of the problems faced remains unclear. These issues require special attention in follow-up and solution-finding, given that the implementation and use of information technology and information systems are the core of smart campus projects. This study analyzes the problem, organizes it more clearly, and identifies the root cause of the problem from scattered issues using Soft Systems Methodology (SSM) integrated with several stages of Root Cause Analysis (RCA). The identified root causes were then mapped into the smart campus dimensions: smart economy, smart society, smart environment, and smart governance. The analysis identified 27 root causes, divided into three categories: human resources, management, and policy. Of these 27 root causes, nine fall within the smart campus dimension, namely the smart economy, smart society, and smart governance subdimensions.